Potential effects of a sugar-sweetened beverages tax on socioeconomic inequalities in health. (30th September 2020) - Djojosoeparto, S K; Eykelenboom, M; Renders, C; Olthof, M R; van Stralen, M M; Steenhuis, I; Poelman, M P; Kamphuis, C B M
Abstract: Background: Sugar-Sweetened Beverages (SSBs) taxes have been implemented in several countries, however, little is known on how an SSBs tax may impact on low and high socioeconomic groups differently. Therefore, the aim of this study was to gain insight into the perceptions of different stakeholder groups in the Netherlands on (1) the contribution of an SSBs tax to socioeconomic inequalities in diet and health and (2) the mechanisms via which an SSBs tax may influence these inequalities. Methods: Semi-structured interviews were held in the Netherlands in March-May 2019 with 27 participants from the following stakeholder groups: health and consumer organisations, health professional associations, advisory bodies, scientists, trade organisations, policy makers, and politicians. Interview transcripts were analysed following a thematic content approach. Results: Participants from all stakeholder groups indicated that an SSBs tax would have a larger impact on the budget and SSB consumption of lower socioeconomic groups. With that, an SSBs tax could have larger health benefits among lower socioeconomic groups as a result of cutting down on SSBs. A few participants - from science and a health professional association - discussed possible unwanted effects of an SSBs tax (e.g. lower socioeconomic groups may compensate their lower SSB consumption with other unhealthy behaviour). Some participants emphasised that an SSB tax should only be introduced when accompanied by other measures (e.g. educational efforts, offering healthy alternatives). Conclusions: Our results imply that most stakeholders agree that an SSBs tax could contribute to a reduction of socioeconomic inequalities in diet and health. However, in order to be effective and to prevent that an SSBs tax leads to a widening of inequalities, it is important to carefully monitor behavioural changes of socioeconomic groups in response to an SSBs tax, and to implement an SSBs tax as part of a comprehensive policy approach. Key messages: An SSBs tax could contribute to a reduction of socioeconomic inequalities in health, according to Dutch stakeholders. It is important to carefully monitor behavioural changes of socioeconomic groups in response to an SSBs tax, and to implement an SSBs tax as part of a comprehensive policy approach.